Sejmy pacyfikacyjne i ich miejsce w ustroju Rzeczypospolitej Obojga Narodów. Rozważania nad sejmami z lat 1589, 1673, 1699 oraz 1736. - Stachurka, Jakub (2023)
The article discusses the topic of pacification sejms in the context of their impact on the systemic transformations of the Polish-Lithuanian Commonwealth and the systemic practice. The author presents what the pacification sejm was, what role it played as a mechanism in the state system and presents the most common goals of constantly calling the parliament with such specific characteristics. Then, in chronological order, the four parliaments from 1589, 1673, 1699 and 1736 are discussed, because only their debates have been completed. The context of the internal situation at the time of calling the pacification is referred to, and then a description of the achievements of the Sejm in the aspect of interest to the author of influencing the shape of the system and provisions deviating from the current custom. In the summary, the author concludes that the pacification parliaments, despite its original character aimed at calming public moods and restoring peace in the country, often became a tool for carrying out certain systemic improvements. So, it is, consequently, a dualism both in purposes and effects. Therefore, these parliaments benefited the Commonwealth as a stabilization instrument and left their certain positive mark on the state system. Beside the Henryk Olszewski brief description of pacificatory sejms and the four monography of successful sejms it is hard to find a synthesis for that specific issue. This is why the author tries to make one universal characteristic of the pacification phenomenon, based on the current state of knowledge and his own conclusions about these specific sejms. Such a trial seems to be necessary when there is currently no holistic definition.
Keywords: pacification; pacificatory sejms; alternate; internal conflict; political reforms; post-election troubles; amnesty